A comparison of feeding hay to steers on bluestem pasture and in drylot - Drake, C.L.; Smith, E.F.; Koch, B.A.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
This study was designed to compare winter bluestem pasture with drylot as a place to winter calves. The same ration, alfalfa and prairie hay, was fed to both groups.
Keywords: Beef; Bluestem pasture; Drylot